A productive research environment: evaluating its characteristics in the UiTM setting - Ab Halim, Roslilee; Abdullah, Hasni (Universiti Teknologi MARA, 2010)
Having the right environment which can stimulate and facilitate research activities is very important to an organization that aims to be productive in producing quality research papers. Many studies concluded that research productivity was affected by both personal characteristics and environmental factors, and some also suggested that environmental factors were the most powerful contributors in influencing research activities. This paper discusses the characteristics of a research-conducive environment as highlighted in various literature reviews and compares these to the Universiti Teknologi MARA (UiTM) setting. It is vital for the staff of UiTM to identify their strengths and weaknesses, so that necessary solutions or actions can be taken in pursuing the goal of becoming a research university.